2014
DOI: 10.1186/1745-6673-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of alcohol and drugs among health professionals in Norway: a study using data from questionnaires and samples of oral fluid

Abstract: Working under the influence of drugs and/or alcohol may affect safety and job performance. However, the size of this possible problem among health professionals (HPs) is unknown. The aim of this study was threefold: (i) to analyze samples of oral fluid and self-reported data from questionnaires to investigate the prevalence of alcohol and drugs among a sample of HPs in Norway, (ii) to study self-reported absence from or impairment at work due to alcohol and/or drug use, and (iii) to examine whether such use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
(41 reference statements)
0
5
1
Order By: Relevance
“…The prevalence of ever consuming alcohol among these study participants is lower than the reported prevalence among Kenyan nurses (35.8%) (Mokaya et al, 2016). It is however higher than the prevalence reported among nurses in Norway, 0.3% (Edvardsen et al, 2014). The prevalence in this study is comparable to the reported prevalence (22%) among healthcare professionals, including nurses in another province of South Africa (Okeke, Ross, Esterhuizen, & Van Wyk, 2012).…”
Section: Lack Of Initiativecontrasting
confidence: 49%
“…The prevalence of ever consuming alcohol among these study participants is lower than the reported prevalence among Kenyan nurses (35.8%) (Mokaya et al, 2016). It is however higher than the prevalence reported among nurses in Norway, 0.3% (Edvardsen et al, 2014). The prevalence in this study is comparable to the reported prevalence (22%) among healthcare professionals, including nurses in another province of South Africa (Okeke, Ross, Esterhuizen, & Van Wyk, 2012).…”
Section: Lack Of Initiativecontrasting
confidence: 49%
“…More detailed results from one business area (healthcare) have been published in an separate article [ 28 ]. In this article we present the total findings from the pilot and main studies, which included 2437 employees from eight business areas.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and drug problems should be considered as health problems and they should be dealt with the same way as any other health problem at work [43]. In Norway, WDT is mainly done within the transport, petrochemical, shipping, automobile, pharmaceutical and computer industries, by mutual agreement between the employee and the company [44].…”
Section: Workplace Drug Testingmentioning
confidence: 99%